Evaluation of Stability of Surface-Treated Mini-Implants in Diabetic Rabbits. (28th May 2014) - Oh, Nam-Hee; Kim, Eun-Young; Paek, Janghyun; Kook, Yoon-Ah; Jeong, Do-Min; Cho, Il-Sik; Nelson, Gerald
Abstract : Introduction . The purpose of this study was to investigate effects of surface treatment of mini-implants in diabetes-induced rabbits by comparing osseointegration around mini-implants. Methods . Twelve New Zealand white rabbits were divided into two groups (alloxan-induced diabetic group and control group). A total of 48 mini-implants were placed after four weeks of diabetic induction. 24 mini-implants were surface-treated with SLA (sandblasted with large grit, and acid etched) and the remaining 24 mini-implants had smooth surfaces. Four weeks after placement, 32 mini-implants were removed from 4 control and 4 diabetic rabbits. Insertion and removal torques were measured. The remaining 16 mini-implants from the two groups were histomorphometrically analyzed. Results . Maximum insertion torque showed no difference between diabetic and control groups, but total insertion energy was higher in control group. In surface-treated mini-implants, maximum removal torque was higher in both diabetic and control groups. Bone-implant contact (BIC) was increased in the control group when compared to the diabetic group. Surface-treated group had higher BIC than smooth surface group in both control and diabetic groups. However, there was no significantly statistical difference. Conclusions . Type 1 diabetes mellitus and surface treatment method of mini-implant affected primary stability of mini-implants. In addition, the use of orthodontic mini-implants in a diabetic patient is likely to show results similar to the healthy patient.